Putaminal mosaic visualized by tyrosine hydroxylase immunohistochemistry in the human neostriatum. - Ryoma eMorigaki (Frontiers in Neuroanatomy, 2016)
Among the basal ganglia-thalamocortical circuits, the putamen plays a critical role in the ‘motor’ circuits that control voluntary movements and motor learning. The human neostriatum comprises two functional subdivisions known as the striosome (patch) and matrix compartments. Accumulating evidence suggests that compartment-specific dysregulations of dopamine activity might be involved in the disease-specific pathology and symptoms of human striatal diseases including movement disorders. This study was undertaken to examine whether or how striatal dopaminergic innervations are organized into the compartmentalized architecture found in the putamen of adult human brains. For this purpose, we used a highly sensitive immunohistochemistry technique to identify tyrosine hydroxylase (TH, EC 1.14.16.2), a marker for striatal dopaminergic axons and terminals, in formalin-fixed paraffin-embedded tissues obtained from autopsied human brains. Herein, we report that discrete compartmentalization of TH-labeled innervations occurs in the putamen, as in the caudate nucleus, with a higher density of TH labeling in the matrix compared to the striosomes. Our results provide anatomical evidence to support the hypothesis that compartment-specific dysfunction of the striosome-matrix dopaminergic systems might contribute to the genesis of movement disorders.